COMMUNITY RESPONSE RELATED TO ADDITION OF SERVICE HOURS IN PUBLIC HEALTH CENTER SEMARANG CITY - Ayu Dyah Pramesti; Septo Pawelas Arso; Nurhasmadiar Nandini (Jurnal Kesehatan Masyarakat (Undip), 2020)
Public Health Center as a health facility provides access to health for individuals and groups. One of the innovations of the Semarang City Health Office in expanding community access to health services is the "5G" Public Health Center, one of which is the Simplicity Service with public health center service hours added so that the public health center is open until evening (07.00-17.00 WIB). The addition of Public Health Center service hours at the Pudakpayung Public Health Center was considered ineffective because patients who visited during the addition of service hours did not reach 10 people and there were still many obstacles in the management of human resources, financing, and the operational system of the Public Health Center. The purpose of this study was to evaluate the implementation of the program in addition to Public Health Center service hours at the Pudakpayung Public Health Center with an approach of 4 health functions and 3 health goals supported by 6 building blocks. This research method was qualitative with in-depth interviews. The respondents were Head of Public Health Center, Financial Manager and Service Manager of Pudakpayung Public Health Center, Head of Health Services in Semarang City Health Office and patients. The results of this study indicate that there were problems with inadequate resources, insufficient funds, the form of services provided is not the same, there was no specific SOP that regulates the addition of Public Health Center service hours, and monitoring evaluation has not been done by Public Health Center or Semarang City Public Health Office. The socialization has been carried out, but the number of morning patients is still much more than the number of patients in the afternoon. This is a challenge for the Public Health so that it can shift patients who visit in the morning to the afternoon.